Reading through esp in an undergraduate law program (2014)
This article presents the results of a study conducted among a group of law students in fift h-level English at a Colombian private university, which analyzed the effects of applying reading through English for Specific Purposes under the criteria of the communicative approach. Data were collected through semi-structured interviews, the students’ oral and written samples and the researcher’s journals. Findings show that specialized reading motivates students to increase both vocabulary and knowledge about their own field of study and also encourages them to use English in everyday situations.En este artículo se presentan los resultados de una investigación llevada a cabo en una universidad privada colombiana, con estudiantes de quinto nivel de inglés del programa de derecho, cuyo propósito era analizar los efectos de aplicar lectura a través del inglés con propósitos específicos bajo el criterio de un enfoque comunicativo. Los datos fueron recolectados a través de entrevistas semi-estructuradas, reportes orales y escritos de los estudiantes y el diario del profesor. Los resultados muestran que la lectura especializada motiva a los estudiantes a ganar vocabulario y conocimiento acerca de su propio campo de estudio, a la vez que los anima a usar el inglés en situaciones reales.